A rare intravenous paraquat exposure presenting with novel and atypical severe clinical manifestations - Vrushali M. Patil; Shirish Shantaram Inamdar; Nikhil Sunil Jadhav; Dipak Pralhad Mali (Indian Journal of Pharmacology, 2026)
Abstract: Paraquat is a highly toxic bipyridyl herbicide that continues to be used in several countries despite restrictions elsewhere. While ingestion is the most common route of poisoning, intravenous administration is rare and associated with extremely high mortality. We report the case of a 26-year-old male who attempted suicide by self-injecting 10 mL of 24% paraquat dichloride intravenously into the dorsal metacarpal region. Within hours, he developed hematemesis, diaphoresis, giddiness, chills, agitation, and diffuse burning sensations. On admission, he was alert but drowsy with bradycardia, pedal edema, and local swelling at the injection site. Laboratory findings revealed leukocytosis, elevated serum creatinine, hypokalemia, and metabolic acidosis. Despite early hemodialysis, continuous renal replacement therapy, and administration of antioxidants and supportive treatment, the patient developed progressive respiratory distress, refractory hypotension, and recurrent cardiac arrests. He died 28 h after admission. Intravenous paraquat poisoning is rare but uniformly fatal. This case emphasizes the importance of early recognition, aggressive supportive care, and the continued need for preventive strategies and regulatory measures to limit paraquat availability.